A comparison of two in vitro bioassays to detect resistance of the cattle tick Rhipicephalus microplus to fipronil - Torrents, Jorgelina; Morel, Nicolas; Rossner, Maria Victoria; Martinez, Norberto Claudio; Nava, Santiago (Elsevier, 2022)
The aim of this work is to compare the sensitivity of two in vitro bioassays to detect resistant to fipronil in Argentinean populations of the cattle tick Rhipicephalus microplus. Two different larval bioassays prepared with technical grade (97%) fipronil were compared: larval immersion test (LIT) and larval packet test (LPT). Seven strains from different provinces were treated with both assays. Colonia Tabay, Colonia Benítez, Intiyaco and Quimili strains were considered resistant in both LIT and LPT bioassays. The 95% confidence intervals (IC95) for lethal concentration 50% (LC50) did not overlap with the susceptible reference strain (SRS) and all the values of RR50 obtained were higher than 2. Garabato and Federal strains were considered as susceptible for both techniques because the IC95 for the LC50 overlapped with those of the SRS and the RR50 values were lesser than 2. An ambiguous situation occurs with Reconquista strain. This strain was considered as susceptible with LPT and with incipient resistant after LIT trial. The analysis of the results indicates that both LIT and LPT trials have enough sensibility to differentiate resistant and susceptible strains, but LIT was more sensitive than LPT when the resistance is incipient.